2008
DOI: 10.1038/ng.141
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and functional impact of DNA copy number variation in the rat

Abstract: The abundance and dynamics of copy number variants (CNVs) in mammalian genomes poses new challenges in the identification of their impact on natural and disease phenotypes. We used computational and experimental methods to catalog CNVs in rat and found that they share important functional characteristics with those in human. In addition, 113 one-to-one orthologous genes overlap CNVs in both human and rat, 80 of which are implicated in human disease. CNVs are nonrandomly distributed throughout the genome. Chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

45
146
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(191 citation statements)
references
References 42 publications
45
146
0
Order By: Relevance
“…That will make it straightforward to test suggestive breed-specific CNVs for particular disease associations. As was demonstrated in rats, is it also feasible to integrate genome-wide information on Quantitative Trait Loci, breed-specific CNV, and gene expression in order to identify candidate genes (Guryev et al 2008). Another use of CNV information is in comparative genetics.…”
Section: Org Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…That will make it straightforward to test suggestive breed-specific CNVs for particular disease associations. As was demonstrated in rats, is it also feasible to integrate genome-wide information on Quantitative Trait Loci, breed-specific CNV, and gene expression in order to identify candidate genes (Guryev et al 2008). Another use of CNV information is in comparative genetics.…”
Section: Org Downloaded Frommentioning
confidence: 99%
“…Recent findings revealed that DNA structural variation (SV) is common in normal rodents (Graubert et al 2007;Guryev et al 2008) and primates (Iafrate et al 2004;Sebat et al 2007; Lee et al 2008; for review, see Freeman et al 2006). The term SV and its subset of copy number variation (CNV), refer to alterations from 1 kb to multi-Mb.…”
mentioning
confidence: 99%
“…Copy-number variations have been shown to be associated with complex traits in several species, including chimpanzee (Perry et al 2008), rat (Guryev et al 2008) and mouse (Adams et al 2005), and in livestock species such as cattle (Liu et al 2010;Hou et al 2011), goat (Fontanesi et al 2010), sheep (Fontanesi et al 2011) and horse (Dupuis et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that copy number variability is a common feature of a wide range of species, from flies (Dopman and Hartl 2007) to maize (Schnable et al 2009), and including mice (Egan et al 2007;Graubert et al 2007;Cahan et al 2009), rats (Guryev et al 2008), dogs (Chen et al 2009), pigs (Ramayo Caldas et al 2010), goats (Fontanesi et al 2010), macaques , and chimpanzees . CNVs have been associated with traits of evolutionary interest, especially human disease-related traits (see, e.g., Craddock et al 2010, and references therein), but also traits in other species such as breed-specific features in dogs (Chen et al 2009), metabolic traits in mice (Orozco et al 2009), and, possibly, phenotypic differences in inbred lines of maize (Schnable et al 2009).…”
mentioning
confidence: 99%